Knowledge, Attitude, and Perception: Impact on Online Ojek Driving Safety - Silalahi, Siska Amonalisa; Thabah, Asep Ali; Irenita, Novembriani (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The high number of accidents for ojek online motorcycle users cannot be separated from the behavior of the riders. Motorist behavior factors have an important contribution in determining the occurrence of road user traffic accidents. Thus, the purpose of this study is to ascertain how knowledge, attitudes, and perceptions will affect motorcycle safety riding behavior in Jakarta in 2023 when it comes to ojek online. This study used survey method with quantitative research data. The population in this study was all ojek online motorcycle drivers in Jakarta and the sample used amounted to 100 respondents. The results of the analysis, computations, and talks demonstrate that knowledge, attitudes, and perceptions all work together to influence Jakarta ojek online motorbike riders’ safety riding behavior positively and significantly. Where partially the variable knowledge has a positive and significant influence on the safety riding behavior of ojek online motorcycle taxis in Jakarta. The same thing with attitude variables that have a positive and significant influence on ojek online motorcycle safety riding behavior in Jakarta. Similarly, the perception variable significantly and favorably affects Jakarta motorbike riders' safety-riding habits (Ojek Online).